1978
DOI: 10.1071/bi9780649
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Patterns of Ovarian Follicle Growth and Ovulation Rate in Sheep

Abstract: The number and growth rate of follicles within classes based on granulosa volume were determined for ovaries taken from groups of 4-5-year-old,. fine-wool Merino ewes drawn at different times of the year from a single strain flock maintained at Armidale, N.S.W:The breeding season of the flock normally extends from February to October and the mean ovulation rate rises from about 0·5 in February to about 1·8~1·9 during April-May.Ewes sampled when they were anoestrous or had one (single-ovulatory) or two (twin-ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…This is further supported by data involving light treatments (Kooistra and Ginther, 1975) (Driancourt, Mariana and Palmer, 19821. In contrast, the close values among the three groups of the mitotic index of antral follicles were expected since a similar fact has been demonstrated in ewes (Turnbull et al, 1978 ;Cahill and Maul6on, 1980 …”
mentioning
confidence: 77%
See 1 more Smart Citation
“…This is further supported by data involving light treatments (Kooistra and Ginther, 1975) (Driancourt, Mariana and Palmer, 19821. In contrast, the close values among the three groups of the mitotic index of antral follicles were expected since a similar fact has been demonstrated in ewes (Turnbull et al, 1978 ;Cahill and Maul6on, 1980 …”
mentioning
confidence: 77%
“…Thus, as in ewes (Turnbull et al, 1978 ;Cahill and Mauleon, 1980), the only part of folliculogenesis lacking during winter is preovulatory development. Furthermore, anestrous follicles seem to be sensitive to endogenous or exogenous hormones since Oxender, Noden and Hafs (1977) have noticed some spikes of estradiol-17(3, and ovulation has been successfully induced with pituitary extracts in a fortnight in seasonally anovulatory mares (Douglas, Nuti and Ginther, 1974 ;Lapin and Ginther, 1977).…”
mentioning
confidence: 99%
“…Using the latter model, we found that the follicular population and the ovarian status are not strongly depressed. As in the ewe, preovulatory follicles are lacking (Cahill, 1979b ;Turnbull et al, 1979), and the size of the largest follicle is highly variable (Sharp, 1975). With the exception of data from Freedman, Garcia and Ginther (1977) (Peters et al, 1975) or ewes either in vivo (Turnbull et al, 1977) (Lushbauch, 1956 ;Mazia, 1961 ;Turnbull et al, 1977 ;Cahill, 1979 mostly lie between these.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive morphological studies of follicle populations in sheep with genetically determined differences in ovulation rate have been reported (Turnbull, Braden & Mattner, 1977;Turnbull, Mattner, George & Scaramuzzi, 1978;Cahill, Mariana & Mauléon, 1979;Cahill, 1981). The distribution of follicle populations in Romanov sheep shows them to have increased numbers of antral follicles and decreased numbers of primordial follicles.…”
Section: Patterns Of Follicular Growthmentioning
confidence: 99%